Reflexões sobre a importância do jogo na educação matemática - Maia, Maria Vânia Moreira (2012)
This dissertation aims to present reflections on the importance of play as a teaching tool in mathematics education, a proposal that the fundamental and necessary curriculum of initial training courses for Universities, which provide a more adequate preparation of future teachers of mathematics. The teaching of mathematics is currently designed as an educational logical mechanism by which exercise is thought, through activities grounded in human experience and mathematical knowledge, which covers both language and everyday practices. However, while the learning of mathematics proves attractive and attracts attention of some students, others may arouse fear and loathing. Thus, for many, the inclusion (or not) of mathematical knowledge in school context may constitute a constraint, generating rejection and use a null. Thus, to reiterate the questions about the limits of construction included in the types of ownership of that knowledge. The current flow convergence educational and pedagogical content analysis suggest one can understand the social situation of the student, as well as their ideas, advocating the use of the game as a teaching resource that will contribute to the child's cognitive development, and propose a teaching of mathematics that will highlight the more concrete situations.